2021
DOI: 10.23876/j.krcp.21.044
|View full text |Cite
|
Sign up to set email alerts
|

Mixed- versus predilution hemodiafiltration effects on convection volume and small and middle molecule clearance in hemodialysis patients: a prospective randomized controlled trial

Abstract: Background: The use of newly developed mixed-dilution hemodiafiltration (HDF) can supplement the weaknesses of pre-and postdilution HDF. However, it is unclear whether mixed-HDF performs well compared to predilution HDF. Methods: We conducted a prospective, open-labeled, randomized controlled trial from two hemodialysis centers in Korea. Between January 2017 and September 2019, 60 patients who underwent chronic hemodialysis were randomly assigned at a 1:1 ratio to receive either predilution HDF (n = 30) or mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Clinical and corporal composition data collected from the institutional medical record were as follows: age, sex, primary kidney disease, dialysis vintage, presence of diabetes, pre‐ and post‐dialysis weight, and post‐dialysis body mass index (BMI), Kt/V urea , serum albumin, creatinine, phosphate, calcium, magnesium and C‐reactive protein (CRP), normalized protein catabolic rate (nPCR), 9 geriatric nutritional index (GNRI), 10 cholesterols and triglycerides. Dialysis conditions comprising time, substitution volume, blood flow, dialysate flow, ultrafiltration volume (UF), intradialytic weight loss and CV (UF + substitution volume) 11,12 were collected. Same day body composition data assessed 30 min after Post‐OL‐HDF sessions using a bioimpedance spectroscopy device (BCM®: Fresenius Medical Care, Buzen city, Japan) were also collected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and corporal composition data collected from the institutional medical record were as follows: age, sex, primary kidney disease, dialysis vintage, presence of diabetes, pre‐ and post‐dialysis weight, and post‐dialysis body mass index (BMI), Kt/V urea , serum albumin, creatinine, phosphate, calcium, magnesium and C‐reactive protein (CRP), normalized protein catabolic rate (nPCR), 9 geriatric nutritional index (GNRI), 10 cholesterols and triglycerides. Dialysis conditions comprising time, substitution volume, blood flow, dialysate flow, ultrafiltration volume (UF), intradialytic weight loss and CV (UF + substitution volume) 11,12 were collected. Same day body composition data assessed 30 min after Post‐OL‐HDF sessions using a bioimpedance spectroscopy device (BCM®: Fresenius Medical Care, Buzen city, Japan) were also collected.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-OL-HDF, pre-dilution online haemodiafiltration; Convection volume = ultrafiltration volume + substitution volume; OH, overhydration (excess fluid = difference between normal extracellular water and measured extracellular water). 13 + substitution volume) 11,12 were collected. Same day body composition data assessed 30 min after Post-OL-HDF sessions using a bioimpedance spectroscopy device (BCM ® : Fresenius Medical Care, Buzen city, Japan) were also collected.…”
Section: Methodsmentioning
confidence: 99%
“…Corrected convection volume was calculated in liters (L) by adding the substitution volume to the net ultrafiltration volume removed during the session. When pre-dilution method was used, the substitution volume was divided by half to account for the reduced clearance associated with this method in accordance to usual practice in patients with end-stage kidney disease 25,26,27 .…”
Section: Exposures Outcomes and Definitionsmentioning
confidence: 99%
“…In this issue of Kidney Research and Clinical Practice, Park et al [8] conducted a randomized controlled trial to compare convection volume and solute clearance between predilution HDF and mixed dilution HDF in patients receiving maintenance HD. The mixed dilution mode was not inferior to the predilution mode considering effective convection volume (51.5 ± 9.0 L/session vs. 41.0 ± 10.3 L/session, respectively).…”
mentioning
confidence: 99%
“…Since predilution HDF uses twice as much replacement fluid as the postdilution mode, the effective convection volume for mixed dilution HDF can be calculated as follows as the authors suggested: effective convection volume = substitution volume in predilution mode + (2 × substitution volume in postdilution mode) + ultrafiltration volume [8]. In this regard, the effective convection volume can be used instead of absolute convection volume when comparing the convection volumes between predilution and mixed dilution HDF.…”
mentioning
confidence: 99%